Exploring the diversity and metabolic potential of actinomycetes from cassava wastewater - Awoniyi, Marcus (2021)
The processing of cassava results in the creation of a considerable amount of waste effluent. Understanding the indigenous microbial diversity proved to be a useful approach in investigating cassava effluent use for biodiesel production. We compared the diversity from cassava effluent using culture-dependent and culture-independent approaches using selective media and amplicon sequencing to target actinobacteria. Actinobacteria are producers of various useful metabolites, with some members in this phylum known for their oleaginicity. Arginine Glycerol Salt (AGS), Glycerine Asparagine Agar (GA) and Starch Casein Agar (SCA) were the most suitable media to enumerate the diversity in cassava effluent from this study. Streptomyces, Micromonospora and Micrococcus were the predominant actinobacteria detected by culture-dependent approach. In concurrence to culture-dependent approach, the culture-independent method also revealed various genera related to actinobacteria. In the culture-independent approach, Bifidobacterium, Corynebacterium and Micromonospora were found to be the dominant genera. The washing and pressing stages in cassava production had a more significant proportion of the actinobacteria from both methods adopted. Holistically, both approaches provided complementary information inferring the diversity within samples. The functional potential of novel isolates from cassava waste effluent (Streptomyces and Micromonospora) was further explored for triacylglyceride (TAG) synthesis and accumulation. Phenotypic characteristics of isolates involving growth requirement, the enzymatic profile, resistance of isolates to various antibiotics, degradation of complex compounds, carbon and nitrogen utilization were explored to reveal the physiological properties useful in biodiesel production. The fatty acid methyl ester (FAME) profiles of Micromonospora and Streptomyces represented a significant percentage of branched-chain fatty acids (BCFAs). Thin-layer chromatography, viable colony staining methods based on Nile Red, inferred TAG accumulation by novel Cassava wastewater (CWW) isolates. Further investigation into the key Kennedy pathway suggested that alternative pathways might be involved in TAG synthesis within Micromonospora and Streptomyces isolates. The presence of PAP multifunctional gene lppα (SCO1102) and lppβ (SCO1753) involved in Diacylglycerol (DAG) synthesis within Streptomyces CWW isolate and Streptomyces albidoflavus support this hypothesis.